Gestión de los residuos de aparatos eléctricos electrónicos comercializados en la ciudad de Nauta, en base a la Norma Técnica Peruana 900.064:2012. Loreto-2021 - Alvear Fonseca, David Eli (2022)
This research corresponds to a descriptive, cross-sectional statistic that deals with the management of waste from electronic electrical devices sold in the city of Nauta, based on the Peruvian Technical Standard 900.064:2012. Loreto-2021”. A simple probabilistic sample was used, where 80 people who live in the central area of the city of Nauta were chosen. They conclude that the handling and management of WEEE in the town of Nauta are not treated in an environmentally adequate manner, therefore, they do not comply with the provisions of NTP 900.064:2012, due to: 50% of the people in the study, the disposes as household solid waste, unused appliances are kept in their homes (6.25%) and 18.75% sell the appliances to recyclers. (87.5%) of those surveyed do not specify whether these equipment can be reused; they have no knowledge about the effect on health and the environment (87.5%), and that if there were an impact, it would be minimal (62.5%). They also refer that they do not know the name of WEEE in its entirety. They discarded appliances in their homes (two years ago), computer equipment and telecommunications (cell phones) 50% and some electrical and consumer appliances such as radios, batteries or batteries (20%), 13.75% lighting fixtures, 10% small household appliances, such as irons, clocks, etc. Likewise, in their workplaces, they mostly discarded computer and telecommunications equipment (50%) and lighting devices (43.75%), generally because they no longer work (62.5%) and others because of the space they occupy, in addition there are no spare parts, due to their age. As for RAE distributors, marketers and repair shops, they know a lot (30%) to a lot (40%) of WEEE, likewise they are not aware of laws or regulations that establish the management and handling of this equipment (70%).